Determination of velocity profiles of Bird-Carreau fluids in curvilinear microchannels using random sample consensus - Yoon, Kyu; Jung, Hyun Wook; Chun, Myung-Suk (KOREAN SOC RHEOLOGY, 2020)
Flow features of rheologically complex fluids inside curved microchannels should be meaningfully scrutinized for effective mixing, sorting, and manipulation of nano- and micro-sized colloids or particles. In this study, a particle streak velocimetry method with coordinate transformation is incorporated to depict experimentally the axial velocity profiles of Newtonian and non-Newtonian (Bird-Carreau, BC) fluids in a curvilinear microchannel under constant flow rate conditions. Theoretical velocity distributions for both fluids are favorably substantiated from experimental observations that employ a random sample consensus (RanSAC) algorithm under various channel geometric conditions, demonstrating the good agreement between experiments and simulations previously developed. It is confirmed that the BC fluid showed blunt and non-parabolic profiles in comparison to the Newtonian case at a low Dean number. The suggested algorithm and method for accurately observing microscale flow fields provide useful insights into the elaborate manipulation and processing of non-Newtonian fluids in curved channel devices.
Keywords: FLOWS; SUSPENSION; DEVICES; MODEL